Imatinib and hypophosphatemia: Case report and review of literature - Erdem Şen; İrem Öner; Özlem Ata (Journal of Oncological Sciences, 2017)
Imatinib mesylate is a potent inhibitor of the BCR-Abl kinases, c-Kit, PDGFR, and fms. Imatinib used for treatment of chronic myeloid leukemia and gastrointestinal stromal tumor. Imatinib has been well tolerated. The most common adverse events reported included edema, nausea, diarrhea, myalgia or musculoskeletal pain, fatigue, dermatitis or rash, headache and abdominal pain. Hypophosphatemia is rare side effect of imatinib treatment. This is the report of a case experiencing severe hypophosphatemia during adjuvant treatment with imatinib for gastrointestinal stromal tumor.